Contemporary collecting: objects, practices, and the fate of things - Moist, Kevin M; Banash, David (The Rowman & Littlefield Publishing Group, 2013)
While the importance of collections has been evident in the sciences and humanities for several centuries, the social and cultural significance of collecting practices is now receiving serious attention as well. As reflected in programs like Antiques Roadshow and American Pickers, and websites such as eBay, collecting has had a consistent and growing presence in popular culture. In tandem with popular collecting, institutions are responding to changes in the collecting environment, as library catalogs go online and museums use new technologies to help generate attendance for their exhibits. In Contemporary Collecting: Objects, Practices, and the Fate of Things, Kevin M. Moist and David Banash have assembled several essays that examine collecting practices on both a personal and professional level. These essays situate collectors and collections in a contemporary context and also show how our changing world finds new meaning in the legacy of older collections. Arranged by such themes as “Collecting in a Virtual World,” “Changing Relationships with Things,” “Collecting and Identity—Personal and Political,” and “Collecting Practices and Cultural Hierarchies,” these essays help illuminate the role of objects in our lives. Covering a breadth of interdisciplinary perspectives and subjects—from PEZ candy dispensers and trading cards to sports memorabilia and music—Contemporary Collecting will be of interest to scholars of cultural studies, anthropology, popular culture studies, sociology, art history, and more.